2021
DOI: 10.3390/agriculture11121282
|View full text |Cite
|
Sign up to set email alerts
|

Ash Melting Behavior of Rice Straw and Calcium Additives

Abstract: Rice straw is potentially an appropriate feedstock material for biofuel production, since a huge amount of this postharvest residue is generated every year. The transformation of such agricultural biomass into densified products with a higher energy value and their subsequent combustion is associated with several questions. One of them is that rice straw exhibits a large formation of ash during combustion; thus, it is essential to know the nature of its ash melting behavior. Generally, during the combustion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Chaloupková et al [18] prepared ash from rice straw at 550 • C in a muffle furnace. Ash melting temperatures were determined according to the ČSN P CEN/TS 15370-1:2007, and ash was prepared according to EN ISO 18122:2015.…”
Section: Introductionmentioning
confidence: 99%
“…Chaloupková et al [18] prepared ash from rice straw at 550 • C in a muffle furnace. Ash melting temperatures were determined according to the ČSN P CEN/TS 15370-1:2007, and ash was prepared according to EN ISO 18122:2015.…”
Section: Introductionmentioning
confidence: 99%
“…In sample WT-275-30, the ash content was 24.14% wt. Such a high ash content can be problematic, depending on the type of combustion device, as was observed during the processing of residues from rice cleaning [ 56 ]. The reason for the increase in ash content is the loss of mainly moisture but also oxygen and hydrogen during torrefaction.…”
Section: Resultsmentioning
confidence: 99%
“…The rice husk contains approximately 75% organic volatile matter, and the remaining 25% of its weight is converted into ash, which is known as rice husk ash (RHA), during the incineration process [ 119 ]. The high ash content, which has a range of 9–22% [ 120 , 121 , 122 ], and remaining chemical make-up of RH mean that rice husk combustion faces some challenges. For instance, the high amount of silica and sulphur, along with alkali metals and alkaline earth metals, present in RH poses a threat to its combustion, as it leads to the low melting temperature of ash followed by slag generation and fouling [ 120 , 122 , 123 ].…”
Section: Valorization Of Rice Residuesmentioning
confidence: 99%
“…The high ash content, which has a range of 9–22% [ 120 , 121 , 122 ], and remaining chemical make-up of RH mean that rice husk combustion faces some challenges. For instance, the high amount of silica and sulphur, along with alkali metals and alkaline earth metals, present in RH poses a threat to its combustion, as it leads to the low melting temperature of ash followed by slag generation and fouling [ 120 , 122 , 123 ]. Moreover, it has been found that the influence of ash on thermal behaviour is directly related to the amount of potassium in the feedstock.…”
Section: Valorization Of Rice Residuesmentioning
confidence: 99%